Analisis Pengelolaan Dana Zakat Terhadap Pemberdayaan Masyarakat Pada BAZNAS Kota Bogor - Dede Sulaeman; Amie Amelia; Yayat Sujatna; Saiful Anwar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Zakat is an important instrument in wealth redistribution and community empowerment in the context of Islamic economics. In this context, research on the management of zakat funds by the National Zakat Agency (BAZNAS) of Bogor City is very relevant. This study aims to analyze the effectiveness of zakat fund management and its impact on community empowerment. The research methods used are qualitative and quantitative approaches, involving data collection through interviews, surveys, and documentation studies. The results of the study indicate that BAZNAS Bogor City has succeeded in managing zakat funds well. The significant allocation of funds for empowerment programs, such as skills training and business capital assistance, is one indicator of this success. For example, the sewing training program held by BAZNAS has helped many women in Bogor to acquire new skills, so that they can be financially independent and contribute to the family economy. However, the challenges faced by BAZNAS cannot be ignored. The lack of public awareness of the importance of zakat and transparency in fund management are issues that need to be addressed. Many residents still do not understand the benefits of zakat, so their participation in these programs is low. In addition, transparency in the use of zakat funds is also in the spotlight, because the community has the right to know how the funds they donate are used for the common good. To overcome these challenges, this study recommends increasing socialization of zakat, both through public campaigns and collaboration with various parties, including educational institutions and community organizations. By increasing public awareness and ensuring transparency in management, it is hoped that the positive impact of zakat management can be maximized.